S108. THE RELATIONSHIP BETWEEN CHANGE IN THE CGI AND CHANGE IN THE PANSS VARIES BY REGION. (9th April 2019) - Daniel, David; Kott, Alan
Abstract: Background: We and others have previously demonstrated regional differences in measurement of psychiatric symptoms and in the relationship between the CGI and PANSS. Global clinical trials in schizophrenia pool data utilize the Clinical Global Impression (CGI) to assess overall severity of illness. We hypothesized that the schizophrenic symptoms driving change in the CGI would vary with regional norms impacting perceptions of psychiatric disability. Methods: In this post-hoc analysis, 29, 640 visits generated in eight phase 2 and phase 3 acute schizophrenia studies were analyzed. We assessed whether the relationship between the change in the CGI-S and the change in schizophrenic symptoms measured by the PANSS varied among geographic regions Asia (n=1, 661 pairs), Eastern Europe (n=11, 109 pairs) North America (n=6, 969 pairs) and South America (n=607 pairs). The relationship between the CGI-S and 1) PANSS total score, 2) PANSS positive subscale, 3) PANSS Marder negative factor score were examined and correlation coefficients with 95% Confidence intervals between the CGI-S and respective measures were calculated from the data. All raters received standardized training for assessment of the PANSS and CGI-S. Results: The strength of the relationship between change in the CGI-S and the PANSS total PANSS positive subscale and PANSS negative subscale varied by geography. The relationship was strongest in Asia and Eastern Europe and weakest in North and South America. Discussion: The regional differences noted may be due to a combination of cultural differences in what drives improvement in illness severity as well as different levels of familiarity with the CGI instrument.